Recombinant protein production in the filamentous fungus Trichoderma - Wei, Huiling; Wu, Mengyue; Fan, Aili; Su, Haijia (Chinese journal of chemical engineering, 2021)
[Display omitted] •Trichoderma are important workhorses for recombinant protein production.•Trichoderma sp. with better enzyme formula for biomass degradation has been developed.•Trichoderma hosts for high purity enzyme production expanded its application.•State-of-art biotechnologies sped up the development of Trichoderma hosts. Trichoderma is an ascomycete fungal genus widely distributed in the soils. Several species were selected, engineered and utilized for protein production for decades. The high extracellular secretion capability and eukaryotic post-translational modification machinery make Trichoderma spp. particularly interesting hosts. In this review, we summarized the recombinant proteins produced in Trichoderma since 2014, concerning their origins, hosts, promoters, terminators, signal peptides, yields and commonly used media. Meanwhile, strategies and merging trends in protein production and strain engineering are classified and summarized regarding codon optimization, promoter utilization, transcription factor regulation, post-translational modification and proteolytic degradation inhibition. With state-of-art biotechnologies and more available expression platforms, Trichoderma spp. could be more successful hosts to produce recombinant proteins as desired, i.e. better enzyme formula for efficient cellulose degradation or functional protein with high purity and yield.